(untitled) (TEL Tempo, Espaço e Linguagem, 2026)
This article analyzes a 1914 criminal case that occurred in Lagoa Vermelha, Rio Grande do Sul, involving accusations of infanticide against a minor, her sister, and her mother. The records reveal the concealment of the crime, linked to an unwanted pregnancy resulting from incestuous practices within the family, highlighting a childhood marked by violence and silencing. Situated within the History of Crime and Justice, the study contributes to understanding the dynamics of gender, violence, and power in the First Republic.